A Phenomenographic Study of Students’ Experiences and Understanding in Learning the Solar System through the Digital Media “Solar System Exploration” - Bella Merryzca Purnama; Widodo, Wahono; Suryanti, Suryanti; Isbadrianingtyas, Nafi (Lembaga Teewan Journal Solutions, 2026)
The integration of digital technology in elementary education has created new opportunities for supporting students’ conceptual understanding in Science and Social Studies (IPAS) learning. However, previous studies have predominantly focused on measuring the effectiveness of digital media rather than examining how conceptual understanding is formed through students’ learning experiences. This study aimed to explore the process through which conceptual understanding develops within a digital exploration space during solar system learning in elementary school. This study employed a qualitative phenomenographic design involving one classroom teacher and twelve Phase C students at an elementary school in Indonesia. Data were collected through participant observation, semi-structured interviews, and document analysis. The data were analyzed using thematic analysis following Braun and Clarke’s procedures, while trustworthiness was established through triangulation, member checking, and audit trails. The findings revealed that conceptual understanding was formed through four interconnected stages: digital visualization, active exploration, social negotiation, and reflective integration. Digital visualization enabled students to transform abstract astronomical concepts into concrete mental representations. Active exploration encouraged students to construct meaning independently through interaction with digital resources. Social negotiation facilitated conceptual refinement through discussion and collaborative inquiry, while reflective integration supported the development of deeper conceptual connections among scientific phenomena. These processes collectively shifted students’ understanding from rote memorization toward relational and meaningful conceptual understanding. This study contributes a conceptual model explaining how digital exploration spaces function as socio-cognitive learning environments that support conceptual understanding in elementary IPAS learning. The findings provide practical implications for designing technology-enhanced learning experiences that promote exploration, dialogue, and reflection rather than merely delivering information.